SEJARAH PENANAMAN Pinus merkusii DI SULAWESI SELATAN (The History of Pinus merkusii Plantation in South Sulawesi) - , Kaso Rusli ([Yogyakarta] : Fak. Kehutanan UGM, 2000)
This paper describes the history of Pinus merkusii plantation in South Sulawesi. The species was introduced in the first time in six forest districts ofS. Sulawesi in 1932 by the Forest Research Institute. From 1932 to 1968 the planting program P merkusii was still in a small scale. The planting program started to il1crease in a relative large scale in 1967 onward. The program was aimed to reforest unproductive alang-alang grassland and schrubland (belukar). The total P merkusii plantation in S. Sulawesi as of 1997 was more than 165000 ha. The plantation is waiting to be utilized. It is unfortunate that some of the plantations have been illegally felled and replanted with agricultural crops.